2012
DOI: 10.4174/jkss.2012.83.5.288
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative and long-term oncological outcomes of laparoscopic treatment for patients with familial adenomatous polyposis

Abstract: PurposeWe evaluated the short- and long-term outcomes of laparoscopic total proctocolectomy with ileal pouch-anal anastomosis (TPC/IPAA) for treatment of familial adenomatous polyposis (FAP). Also, we assessed the oncologic outcomes in FAP patients with coexisting malignancy.MethodsFrom August 1999 to September 2010, 43 FAP patients with or without coexisting malignancy underwent TPC/IPAA by a laparoscopic-assisted or hand-assisted laparoscopic surgery.ResultsThe median age was 33 years (range, 18 to 58 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…To date, only sparse data have been reported on the occurrence of DT in patients with FAP after laparoscopic surgery. The present study showed an overall incidence of DT of 15·0 per cent after prophylactic surgery, consistent with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…To date, only sparse data have been reported on the occurrence of DT in patients with FAP after laparoscopic surgery. The present study showed an overall incidence of DT of 15·0 per cent after prophylactic surgery, consistent with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…In fact from our data, although limited by the small sample, the operative time, complications, and functional aspects are promising when compared with the major recent reports published in literature about laparoscopic total proctocolectomy [25][26][27][28][29][30][31]. The comparative results are shown in the Table 3.…”
Section: Discussionmentioning
confidence: 45%
“…With the special hand port device, surgeons regain tactile feedback, can complete blunt dissection, retraction, control of bleeding, and organ removal simply [17]. Especially, if the surgeon is inexperienced in laparoscopic operations, HALS in some difficult parts of the operation may be useful [18]. …”
Section: Discussionmentioning
confidence: 99%